Serum investigation of antibodies against porcine circovirus 4 Rep and Cap protein in Jiangxi Province, China - Hu, Xifeng; Ding, Zhen; Li, Yu; Chen, Zheng; Wu, Huansheng (Frontiers in Microbiology, 2022)
In 2019, a novel porcine circovirus 4 was first identified in Hunan province, China. PCV4 circular DNA genome could be detected in both disease and healthy pigs. Recently, the prevalence investigations of PCV4 was analyzed in lots of provinces from both China and South Korea with low positive rate. However, there is no serological data have been performed to examine the prevalence of PCV4 in pigs from Jiangxi province. To address this issue, an indirect anti-PCV4 antibody enzyme-linked immunosorbent assay (ELISA) based on the Cap and Rep protein as the coating antigen was established and applied to explore the serum epidemiology of PCV4 in Jiangxi province. PCV4 His tagged Cap and Rep were purified as an antigen to develop the ELISA detection kit. There was not cross-reaction of Cap/Rep based ELISA with antisera against PCV2, TGEV and PRRSV, indicating a high specificity for this ELISA assay. The intra-assay coefficient variations (CVs) of Cap based were 1.239%-9.796%, Rep based was 1.288%-5.011% and inter-assay of CVs were 1.167%-4.694% and 1.621%-8.979%, respectively, indicating a good repeatability. Finally, a total number of 507 samples from Jiangxi province were collected to test antibody prevalence of PCV4, and 17 (3.35%) and 36 (7.10%) number of the samples were Cap and Rep antibody positive, respectively. Taken together, our established ELISA kit could be used to detect serum of PCV4 antibodies with good repeatability and high specificity. In addition, field samples detection results showed that PCV4 was in a low prevalent in intensive pig farms in Jiangxi Province, China.